Reimagining Social Medicine from the South - Neely, Abigail H. 1979-; Neely, Abigail H. 1979- (Book collections on Project MUSE., 2021)
"Reimagining Social Medicine from the South examines the possibilities and limitations of social medicine from one of its most important origin sites. Through a focus on the communities around the Pholela Community Health Centre in South Africa, the book reveals that the twin focus on physical health and the social factors shaping illness yielded remarkable success. South Africa's broader system of racial capitalism limited the efficacy of health center interventions and ongoing witchcraft illnesses challenged a health care program rooted in biomedicine. To understand both the successes and failures, Reimagining Social Medicine from the South rethinks the concept of the "social" in social medicine. By examining social medicine in depth in this place, this volume reveals that health and illness are the product of relationships among people, things, and harder to categorize beings like ancestors and incantation. In rethinking social life and social medicine from Pholela, Abigail H. Neely offers an alternative to common narratives of social medicine and challenges global health practitioners to recognize and accommodate the multiple worlds and multiple actors that shape health and healing in Africa and beyond"